The Effect of Milk Quality and Feed Consumption Substituted Young Coconut Husk Silage into the Ration of Sapera Goats as a Forage Substitution - Resthu, Muhammad; Ilham, Ilham; Rosita, Ida Rosita; Widayat, Rian Widayat; Aldi, Imammul (Jurnal Sain Peternakan Indonesia, 2024)
This study used a Latin Square Design with four dairy goats and 4 periods. Treatments consisted of P0 = no substitution; P1 = 20% substitution of young coconut husk silage; P2 = 40% substitution of young coconut husk; and P3 = 60% substitution of young coconut husk silage. Data were analyzed using analysis of variance (ANOVA) using SPSS 25, and if a significant effect was found, Duncan's multiple range test (DMRT) was followed. The results showed that there was a substantial difference in the substitution of young coconut husk silage on NFE consumption and CF consumption (P<0.05) and insignificant in fat content and SNF content of Sapera goat milk (P>0.05). In conclusion, the addition of young coconut husk silage as a substitute for forage into the total ration of the best Sapera goats is 40%.